(Dub)smashing the fourth wall the kalyeserye’s metafiction - Del Ocampo, Ivery (2016)
Access online through this link: https://www.plarideljournal.org/article/dubsmashing-fourth-wall-kalyeseryes-metafiction
Keywords: Romance in television; Mendoza, Maine; Richards, Alden; Eat Bulaga! (Television program)